2009
DOI: 10.3892/ijmm_00000187
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome changes induced by docetaxel in human mammary cell lines expressing different levels of ERBB2

Abstract: Abstract. The taxane docetaxel is currently the most effective chemotherapeutic drug for the treatment of advanced breast cancer. However, a considerable proportion of breast cancer patients do not respond positively to docetaxel. The mechanisms of docetaxel resistance are poorly understood. Overexpression of ERBB2 occurs in 15-30% of breast tumors and is associated with chemoresistance to a variety of anticancer drugs. In the present study, we sought to identify genes involved in ERBB2-mediated chemoresistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…These two effectors are also clinically relevant since their mRNA levels in primary tumors can predict the outcome of metastatic colorectal cancer [35]. In two pre-clinical studies, AREG/EREG were not identified as regulated targets by docetaxel treatment [36,37]. However, AREG expression levels have been associated with disease progression of breast cancer or head and neck squamous cell carcinoma in patients receiving a combination treatment of anti-EGFRs and docetaxel [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…These two effectors are also clinically relevant since their mRNA levels in primary tumors can predict the outcome of metastatic colorectal cancer [35]. In two pre-clinical studies, AREG/EREG were not identified as regulated targets by docetaxel treatment [36,37]. However, AREG expression levels have been associated with disease progression of breast cancer or head and neck squamous cell carcinoma in patients receiving a combination treatment of anti-EGFRs and docetaxel [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, abnormal SPARC expression has been associated with tumor characteristics such as growth and metastasis in different cancer types [38]. Previous studies from our group evaluating the gene expression profile in breast epithelial cells with the difference in ERBB2 expression before and after treatment with Docetaxel identified differential expression of SPARC as a potential biomarker of chemosensitivity [39,40]. Subsequently, we investigate the potential prognostic value of the SPARC protein using immunohistochemical analysis on tissue-microarrays.…”
Section: Introductionmentioning
confidence: 98%